KERENTANAN SOSIAL TERHADAP BAHAYA LONGSOR DI KECAMATAN GIRIMULYO, KULON PROGO - Riasasi, Widiyana; Saputra, Ridho Abdhe; Wahyuni, Desri (J SIG (Jurnal Sains Informasi Geografi), 2023)
Landslide is one of the hazards that threatens and has the potential to cause material losses and even fatalities. In 2021, one-third of the disasters in Indonesia are landslides. Landslides are caused by physical factors and human activities. Vulnerability measurement is needed to calculate disaster risk. Geographic Information Systems (GIS) plays a significant role in disaster management because it can provide a spatial and mathematical picture. This study aims to assess the level of vulnerability of society in the social sector to the threat of landslides in Kecamatan Girimulyo, Kulon Progo Regency, Special Region of Yogyakarta Province, which is analyzed spatially. The measurement of social vulnerability follows the guidelines issued by the National Disaster Management Agency using parameters of population density and vulnerable groups. The study area covers four subdistricts, namely Purwosari, Pendowoharjo, Jatimulyo, and Giripurwo. Kecamatan Girimulyo is located in an area dominated by hills and mountains, reaching an altitude of 500 meters above sea level. Data were obtained from the Girimulyo sub-district statistics center and the Geospatial Information Agency. Scoring and weighting methods are used to assess each parameter in order to obtain an index of social vulnerability to landslide threats. The results of the calculation of the population density parameter in Kecamatan Girimulyo show two classes, low and middle. The sex ratio measurement shows that the study area is included in the low class, the vulnerability dependency ratio is included in the middle class, and the classification of the disability ratio is included in the low class. The similarity of the study areas for each parameter indicates that the characteristics of the population are relatively the same or homogeneous. The social vulnerability index in Kecamatan Girimulyo is included in the low category. This indicates that the people of Kecamatan Girimulyo are socially prepared in the event of a landslide.